Microbial Biofortification of Grain Crops: Current State and Prospects - Daria E. Kolpakova; Yuliya R. Serazetdinova; Natalya V. Fotina; Alexandra V. Zaushintsena; Lyudmila K. Asyakina; Anna I. Loseva (Техника и технология пищевых производств)
Hidden hunger is a significant social issue in numerous countries worldwide, causing the development of nutrition-related diseases among populations annually. Biofortification offers a sustainable solution as it combines methods of cross-breeding, genetic engineering, agriculture, and microbiology. The authors reviewed international studies in the field of microbial biofortification in order to assess the microbial potential to enh ance the essential element content in grain crops. The review featured relevant scientific articles published by foreign experts in Scopus, ScienceDirect, and Google Scholar in 1984–2024. The keywords included biofortification, wheat, rice, oats, growth stimulation, antagonism, and phytopathogen. The sources were processed in Zotero and VOSviewer. Nitrogen fixation and nutrient solubilization are the main mechanisms of microbial biofortification. Solubilization occurs as a synthesis of organic and inorganic acids, protons, siderophores, extracellular enzymes, and other secondary metabolites. Microorganisms can improve the expression of plant genes in terms of absorption and nutrient accumulation. They also affect root systems, facilitating the extraction of nutrients from the soil. The authors summarized laboratory and field studies on microbial biofortification of rice, wheat, and barley with iron, selenium, zinc, copper, manganese, nitrogen, phosphorus, and potassium. Biofortified growth-promoting microorganisms are a sustainable, reliable, and cost-effective approach to food security and hidden hunger issues. The review offers relevant information that can be used to develop new microbial preparations for the domestic agriculture.